2010
DOI: 10.1021/ed1000922
|View full text |Cite
|
Sign up to set email alerts
|

Art as an Avenue to Science Literacy: Teaching Nanotechnology through Stained Glass

Abstract: In this article, we describe a series of interdisciplinary activities that highlight the connections between medieval stained glass artistry and nanotechnology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 18 publications
1
39
0
Order By: Relevance
“…
showing different color in reflection and transmission, to the inspiring coloration of ancient church windows, [2] and modern effect pigments [3] that use sparkle, luster, and color travel to create vivid coloration. Aesthetics and function are often intimately linked in modern materials.
…”
mentioning
confidence: 99%
“…
showing different color in reflection and transmission, to the inspiring coloration of ancient church windows, [2] and modern effect pigments [3] that use sparkle, luster, and color travel to create vivid coloration. Aesthetics and function are often intimately linked in modern materials.
…”
mentioning
confidence: 99%
“…For shape-tuned nanoparticles, dissolution in PVA did not counterbalance the shift caused by centrifugation; thus the LSPR of nanoparticles in the film remained at shorter wavelengths than the LSPR of nanoparticles in the mother solution ( Figure 4b). It was previously reported that in order to entrap colored nanoparticles in PVA polymer, solid PVA was dissolved at 80 ºC in a yellow solution of silver nanoparticles for several hours [20]. However, heating resulted in loss of color as PVP does not provide protection from thermal reshaping of nanoparticles [41].…”
Section: Optical Stability During Preparation Of Filmsmentioning
confidence: 99%
“…to the nanocomposite to alter the morphology or coupling of nanoparticles [13,14,15,16]. While, these complex modifications have produced colored films, the simple embedding of silver nanoparticles in films generally produces a single color, yellow [17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In other words, educational objectives represent what is required for students to learn (Anderson et al, 2001). Science outreach programmes list educational objectives within their reports, which range from introducing new concepts (DeWaters and Powers, 2009) to developing inquiry skills through hands on activities (Slezak et al, 2010) and increasing scientific literacy (Duncan et al, 2010). A common point is that they all have the objective 'to enhance students' scientific education'.…”
Section: Educational Objectivesmentioning
confidence: 99%
“…Some science outreach programs were developed to introduce new science concepts or in response to concepts that were poorly assimilated in school (Crane et al, 1994). Duncan et al's (2010) science outreach programme aims to introduce the concept of nanotechnology to primary level students, a concept that is not part of the students' science curriculum. There are also common objectives in outreach programs which promote the re-learning of concepts that are perceived by outreach developers as poorly assimilated by students (Munn et al, 1999).…”
Section: Literacymentioning
confidence: 99%